Impairment of the Ability of HDL From Patients With Metabolic Syndrome but Without Diabetes Mellitus to Activate eNOS: Correction by S1P Enrichment. Issue 5 (May 2017) - Denimal, Damien; Monier, Serge; Brindisi, Marie-Claude; Petit, Jean-Michel; Bouillet, Benjamin; Nguyen, Amandine; Demizieux, Laurent; Simoneau, Isabelle; Pais de Barros, Jean-Paul; Vergès, Bruno; Duvillard, Laurence
Abstract : Objective—: High-density lipoprotein (HDL) from nondiabetic patients with metabolic syndrome (MetS) displays abnormalities in their lipidome, such as triglyceride enrichment and sphingosine-1-phosphate depletion. We hypothesized that these abnormalities could impair the ability of HDL to stimulate endothelial nitric oxide synthase (eNOS). Approach and Results—: Compared with HDL from control subjects, HDL from normoglycemic patients with MetS was 39% richer in triglycerides ( P <0.01) and 15% poorer in sphingosine-1-phosphate ( P <0.05; n=23 in each group). eNOS activity, assessed by the conversion of L-[ 3 H]arginine to L-[ 3 H]citrulline, was 69% lower in human umbilical vein endothelial cells incubated with HDL from MetS patients than in cells incubated with HDL from controls ( P <0.0001). In addition, the activating phosphorylation of eNOS at serine (Ser) 1177 and of Akt (protein kinase B) at Ser473 was 37% ( P <0.001) and 39% ( P <0.05) lower, respectively, with HDL from MetS patients. Sphingosine-1-phosphate enrichment of HDL from MetS patients restored their ability to stimulate eNOS activity ( P <0.05), in relation with a significant increase in eNOS phosphorylation at Ser1177 ( P <0.05) and in Akt phosphorylation at Ser473 ( P =0.05). By contrast, triglyceride enrichment of HDL from control subjects did not modify eNOS activity ( P =0.90) and phosphorylation at Ser1177 ( P =0.87). Conclusions—: We provide evidence that the activation of eNOS by HDL is decreased in MetS patients before the appearance of diabetes mellitus and that sphingosine-1-phosphate depletion of HDL is the main factor responsible for this defect. This has important consequences on the impairment of HDL functionality and antiatherogenic properties in these patients. Abstract : Supplemental Digital Content is available in the text.